Broad distribution and high proportion of protein synthesis active marine bacteria revealed by click chemistry at the single cell level - Samo, Ty J.; Smriga, Steven; Malfatti, Francesca; Sherwood, Byron P.; Azam, Farooq (Frontiers in Marine Science, 2014)
Marine bacterial and archaeal communities control global biogeochemical cycles through nutrient acquisition processes that are ultimately dictated by the metabolic requirements of individual cells. Currently lacking, however, is a sensitive, quick, and quantitative measurement of activity in these single cells. We tested the applicability of copper (I)-catalyzed cycloaddition, or “click”, chemistry to observe and estimate single-cell protein synthesis activity in natural assemblages and isolates of heterotrophic marine bacteria. Incorporation rates of the non-canonical methionine bioortholog L-homopropargylglycine (HPG) were quantified within individual cells by measuring fluorescence of alkyne-conjugated Alexa Fluor® 488 using epifluorescence microscopy. The method’s high sensitivity, along with a conversion factor derived from two Alteromonas spp. Isolates, revealed a broad range of cell-specific protein synthesis within natural microbial populations. Comparison with 35S-methionine microautoradiography showed that a large fraction of the natural marine bacterial assemblage (15-100%), previously considered inactive by autoradiography, were actively synthesizing protein. Data pooled from a large number of samples showed that cell-specific activity scaled logarithmically with cell volume. Assemblage activity distributions of each sample were fit to power-law functions, providing an illustrative and quantitative comparison of assemblages that demonstrate individual protein synthesis rates were commonly partitioned between cells in low- and high-metabolic states in our samples. The HPG method offers a simple potential approach to link individual cell physiology to the ecology and biogeochemistry of bacterial (micro)environments in the ocean.